First record of the squat lobster genus Sternostylus Baba, Ahyong & Schnabel, 2018 (Crustacea: Decapoda: Sternostylidae) in Taiwan - Lin, Chia-Wei; Chan, Tin-Yam (Zootaxa, 2019)
The deep sea squat lobster, Sternostylus hendersoni (Alcock & Anderson, 1899a), is reported for the first time from Taiwan, also representing the first record of the genus from the area. Two specimens of S. hendersoni were collected near a cold-seep area off southwestern Taiwan. Both specimens are females and have similar morphology but different body coloration, with one specimen being reddish orange and the other is pinkish orange. The differences in coloration are illustrated.